2018
DOI: 10.5935/2446-4775.20180010
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mycoplasma activity of Curcuma longa extracts and your isolated compound, the curcumin

Abstract: | www.revistafitos.far.fiocruz.br Avaliação do potencial antioxidante e anti-Helicobacter pylori in vitro de extratos de plantas medicinais utilizadas popularmente na região amazônica ARTIGO DE PESQUISA FARMACOLOGIA Anti-mycoplasma activity of Curcuma longa extracts and an isolated compound, the curcumin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…In the search for new drugs that are effective against bacteria and safe for the environment as well as for humans, well-characterized products of plant origin, including polyphenols, such as curcumin, have been evaluated. Curcumin previously exhibited an antimycoplasmic effect against Mycoplasma hominis, Mycoplasma capricolum, Mycoplasma mycoides, Mycoplasma genitalium, and Mycoplasma pneumoniae at concentrations ranging from 50 to 100 µg mL −1 [11]. We considered the strains that grew at a dilution greater than 2 µg mL −1 as resistant to Mycoplasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the search for new drugs that are effective against bacteria and safe for the environment as well as for humans, well-characterized products of plant origin, including polyphenols, such as curcumin, have been evaluated. Curcumin previously exhibited an antimycoplasmic effect against Mycoplasma hominis, Mycoplasma capricolum, Mycoplasma mycoides, Mycoplasma genitalium, and Mycoplasma pneumoniae at concentrations ranging from 50 to 100 µg mL −1 [11]. We considered the strains that grew at a dilution greater than 2 µg mL −1 as resistant to Mycoplasma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the in vitro antibacterial effect of curcumin on Staphylococcus aureus, Staphylococcus intermedius, Staphylococcus epidermidis, and Edwardsiella tarda [10] have demonstrated that the minimum inhibitory concentration (MIC) of curcumin solubilized in dimethyl sulfoxide against Mycoplasma spp. isolated from mammals ranges from 50 to 100 µg mL −1 [11], although its effect on mycoplasmas isolated from birds has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Diversas atividades biológicas são relatadas a esta planta (MARCHI et al, 2016), em estudos relacionando a estrutura e atividade de derivados de curcumina a fim de produzir moléculas com melhor atividade anticancerígena foi verificado que é possível quando a cadeia de 7-carbonos foi diminuída para 5-carbonos (OHORI et al, 2006). Vários derivados têm apresentado atividade antibacteriana, antiviral e antifúngica (MOGHADAMTOUSI et al, 2014), no teste de microdiluição, demonstrou ter atividade contra cepas de micoplasma (BOEDER et al, 2018), os extratos etanólicos causaram a diminuição da área de lesões da aorta, bem como a diminuição dos níveis de lipídeos in vivo (LIN et al, 2020). Ainda em testes in vivo, também, induziu a angiogenêsis, acelerando dessa forma a cicatrização de lesões causadas em ratos diabéticos (KANT et al, 2015).…”
Section: Introductionunclassified